The Responsibility of Werda Notary to Deals the Problems What Has Done - Shinta Rahmatika Damayanti; Nanang Sri Darmadi (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This study aims to find out and examine how long the Notary is responsible for the deed made after the end of his term of office, as well as to find out and examine how the forms of civil liability of the Notary are to the deeds made after the end of his term of office. This type of research uses normative juridical, which is an analytical perspective. The results showed that the form of notary accountability after a Werda Notary can be divided into 3 (three) including 1) Civil liability of the Notary to the material truth of the deed he has made, 2) Civil criminal liability of the Notary to the material truth of the deed he has made, 3) Notary's responsibility in carrying out the duties of the position are based on the notary code of ethics. Werda Notary who has violated the deed he made and caused harm to the parties may be subject to legal provisions both civil and/or criminal as long as the time limit has not been exceeded as stipulated in the Civil Code Article 1967 and the Criminal Code Article 78 jo 79, if the limit the time period has expired, then the parties can legally no longer file a lawsuit and/or claim the notary's office.